Academic's Perspectives of Quality Assurance System: Case Study at University Of Sri Jayewardenepura, Sri Lanka. - Thalgaspitiya,U.K.; Perera,G.D.N. (National Institute of Development Administration, 2015)
This study provides an in-depth understanding of how academics perceive and experience a quality assurance system in a higher education system (QAS) and investigate the purposes and values of the existing Quality Assurance System (QAS), effectiveness of QAS and the areas requiring improvement of University of Sri Jayewardenepura (USJP). The study was conducted by using a qualitative research method. Primary data collected through interviewing of forty four permanent academic staff members in the USJP. The secondary data were collected from the various sources. A two-level analytical coding approach was used to data analysis purpose. The findings revealed that the meanings and purposes of QAS were ambiguous by the participants. Further, it was found that the system adopted by the USJP were not effective in meeting with the requirements. The implications of these findings are useful to all developers of QAS and the members of the higher education in Sri Lanka.
Keywords: Higher education; Quality Assurance System; University Of Sri Jayewardenepura